Analysis of Clean and Healthy Living Behavior (PHBS) in Household Arrangements in Sei Simpang Dua Village, Kampar Kiri Hilir, Kampar Regency in 2022: Analisis Perilaku Hidup Bersih Dan Sehat (PHBS) Pada Tatanan Rumah Tangga Di Desa Sei Simpang Dua Kampar Kiri Hilir Kabupaten Kampar Tahun 2022 - Risti Fadilla Paramita; Winda Septiani; Yessi Harnani; Riri Maharani (Badnur Medisa Group, 2022)
A person's Clean and Healthy Life Behavior (PHBS) is closely related to improving the health of individuals, families, communities and the environment. The low level of PHBS achievement has obstacles including the lack of public knowledge, the lack of outreach costs for cadres in conducting home visits with PHBS, the lack of family support and the lack of facilities and infrastructure to improve PHBS. This study aims to determine the Clean and Healthy Lifestyle (PHBS) in household arrangements in Sei Simpang Dua Village, Kampar Kiri Hilir, Kampar Regency in 2022. This study used a qualitative analytical research design. With data collection techniques using the Triangulation Method. This research was carried out in January-May 2022 in Sei Simpang Dua Village, Kampar Kiri Hilir Health Center, the informants in this study were 7 people consisting of 1 PJ Kesling, 2 Cadres, 4 people from Sei Simpang Dua Village Community. Data collection by in-depth interviews and observations. The results showed that Sei Simpang Dua Kampar Kiri Hilir Village still had not, still using water that did not meet the requirements, did not have proper latrines so they did defecate in the river. , do not have a garbage disposal, have not implemented the behavior of washing hands when doing something and there is still no eradication of mosquito larvae once a week.